Facial Nerve Functional Outcome with Simple Neuromonitoring Paradigm in 87 Cerebellopontine Angle Tumor Surgeries in a Developing Country - Shah, Poornima A.; Ambekar, Sudheer; Ramdasi, Raghvendra; Banerji, Deepu; Diyora, Batuk (Indian Journal of Neurosurgery, 2025)
With the advent of intraoperative neuromonitoring (IONM), facial nerve (FN) preservation improved to nearly 85% in cerebellopontine tumor (CPA) surgeries. Various parameters, such as FN proximal and distal absolute electromyography (EMG) amplitude, stimulation threshold, proximal-to-distal amplitude ratio, and free-run EMG train time, have been used to predict outcomes but not consistently. Hence the aim of this study is to investigate the outcome of FN function in the immediate postoperative period versus the final outcome at 1-year postop and assess factors affecting it.A total of 87 consecutive patients of CPA tumor surgery were retrospectively analyzed between 2015 and 2023 to allow a minimum 12-month postoperative period. Tumor size, immediate postoperative House–Brackmann (HB) scale, and 1-year postoperative HB scale were analyzed. All patients with HB II and above were advised physical therapy. A statistical analysis was conducted to investigate any relationships with FN outcome.Eighty-seven patients underwent resection; 62% had vestibular schwannoma followed by nearly 9% each of meningioma, trigeminal schwannoma, and epidermoid. In addition, 80.5% were large tumors and did not have any statistical relation with outcome. FN continuity was preserved in all 100% patients. Furthermore, 32 (36.7%) had immediate postop facial paralysis. The severity of immediate postoperative paralysis had a statistically significant correlation with the final FN outcome (p = 0.006). Compliance with physical therapy improved the HB grade in 100.0% of the cases in a statistically significantly manner (p = 0.001).Use of IONM improves FN outcome by enabling anatomical continuity. FN function immediate postop can be used to predict long-term outcome. Counseling for continued physical therapy for at least 1-year postoperative period improves outcomes.
Keywords: cerebellopontine angle tumor; neuromonitoring; facial nerve outcome